MORINGA INCREASES THE HEMOGLOBIN IN POST-PARTUM WOMEN - Yulia Fitri (Institute of Computer Science (IOCS), 2022)
One of the causes of bleeding in postpartum mothers is anemia. Moringa contains iron, vitamin C in high amounts so that it can increase hemoglobin levels in post partum period. The aim of the study was to determine the effect of giving Moringa capsules on hemoglobin levels of postpartum mothers. This study used a Quasi Experimental design with a nonrandomized pretest-posttest design. Samples were 30 post partum women of reproductive age (15 case groups and 15 controls). Hemoglobin was measured using HB Digital. Hemoglobin measurement was carried out 5 times, namely days 1,7,14,21 and 30 post partum. Data analysis using T test and Repeated annova. The results showed that giving 60 mg of Moringa per day significantly increased hemoglobin levels on day 14, 21 and 30 post partum mothers (P = 0.00). Moringa is able to increase hemoglobin levels in postpartum women. Further research is needed on the potential content of active compounds in Moringa plants which are presented in dosage forms other than capsules and powder so that they can be used for more general therapy in the postpartum period.